STRATEGI PENINGKATAN KUALITAS PELAYANAN PRAMUSAJI PADA MASA PANDEMI COVID-19 DI FIRE RESTAURANT W BALI - SEMINYAK - Susi Purniasih; Nyoman Dini Andiani (Universitas Pendidikan Ganesha, 2022)
The study aims to identify the challenges and the strategies to improving the service quality of the waiter/ss in Fire Restaurant W Bali along the Covid-19 pandemic. The research design is qualitative which involving interview, observation, and documentation as the instruments to collect the data. Based on the results, it was found that there were some challenges in the restaurant, such things as operational system, financial issue, and lack of foreign languages knowledge. Some strategies were implemented to overcome the challenges. Those were, Dry eight service training, using SOP, taking care of guest’s needs, and giving appreciation to the waiter.